EFEKTIVITAS PENGGUNAAN BUKU KIA DENGAN E-BOOK TENTANG PENGETAHUAN GIZI IBU HAMIL DI PUSKESMAS PUTRI AYU - Bessek Syahdila; Suryani Suryani; Herinawati Herinawati (NHM PRESS, 2022)
Pregnant women are a group that is most vulnerable to nutritional problems because it can affect the growth and development of the fetus they contain. Nutrition of pregnant women is an important thing that must be met during pregnancy. The purpose of this study is the effectiveness of the use of MCH books compared to ebooks on nutritional knowledge of pregnant women at Putri Ayu Health Center in 2022. This study is a quantitative study using a